Investigating the relationship between luck beliefs causal attributions and well-being through a card game experiment - Kazuhisa Miwa; Wentong Yang; Shota Matsubayashi (Scientific Reports)
Abstract This study investigated the relationship between luck beliefs, causal attribution, and well-being through a card game experiment. Building on the two-factor model of luck beliefs–general belief in luck (Belief in Luck) and personal luck (Personal Luckiness)–this study explored how these beliefs influenced subjective well-being and causal attributions to luck or ability. Participants (N = 441) played a concentration card game against a computer agent with varying memory capacities while evaluating whether their success was attributable to luck or ability. The results supported three key hypotheses: (1) Belief in luck was negatively associated with cognitive well-being, whereas Personal Luckiness positively correlated with both cognitive and affective well-being; (2) Belief in luck predicted higher attribution to luck, whereas Personal Luckiness correlated with both luck and ability attributions; and (3) no consistent relationships between causal attributions and well-being were found. These findings highlight the complex psychological mechanisms that link luck beliefs, causal attribution, and well-being.